Enhanced Techniques for Detecting Promiscuous Mode using Packet Fu and the Metasploit Framework - Partho Pandya; Kashyap Joshi; Kapil Kumar (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This article argues that Thailand’s public-sector digitalisation has so far failed to realise the principles of Digital Era Governance (DEG) because it remains institutionally and politically anchored in New Public Management (NPM) logic. Rather than enabling platform-based integration and citizen-centric services, digital initiatives have often reproduced audit-centric, siloed practices that prioritise measurable outputs and compliance. Using a policy-analytic approach, document review of national strategies and agency plans, and synthesis of recent literature and sectoral case examples; the article identifies three mechanisms by which NPM logic is perpetuated in Thailand’s digital transition: (1) proliferation of discrete applications driven by performance reporting and agency visibility; (2) digital tools as instruments of control and compliance rather than coordination; and (3) governance fragmentation and weak interoperability governance. The paper concludes with targeted policy recommendations to reorient Thailand’s digitalisation toward DEG: consolidate digital architecture around shared platforms and standards, redesign performance regimes to reward integration and outcomes, and strengthen cross-agency data governance.